TINJAUAN YURIDIS TERHADAP KONSEP PERDAGANGAN KARBON SEBAGAI INTERNATIONAL COLLABORATIVE DALAM UPAYA PENYELAMATAN DUNIA DARI PEMANASAN GLOBAL - Laurentia A. Kartika; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2014)
ABSTRACT Global warming and climate change are environment issues that often discussed. One way to handle the problem of global warming and climate change with carbon trading concept as a form of collaborative between developed countries and developing countries conducted by ERPA (Emission Reduction Purchase Agreement) contract has juridical aspects. Problems in this research are: how the rules of international law on global warming, how about international law governing carbon trade, how about the legal aspects of carbon trading-related international cooperation in an effort to cope with the impact of global warming, according to the agreement of ERPA (Emission Reduction Purchase Agreement). This research is a descriptive normative law because the target of this research is reviewing the rule of law that is related to global warming, and carbon trade by using library research techniques. Data were analyzed qualitatively. Global watming and climate change are regulated in The United Nation Framework Convention on Climate Change (UNFCCC). Unfccc become a reference the parties ratified this convention in making the rules further on ways to deal with global warming and climate change. The UNFCCC also became a reference for the establishment of the Kyoto Protocol that come up with the concept of carbon trading through Flexible Mechanism. One of the carbon trading concept is the CDM which allow cooperation between developed countries and developing countries. CDM project conducted by ERPA (Emission Reduction Purchase Agreement). There are some clauses in the contract of ERPA for implementation of CDM project. Projects through carbon trading scheme of the CDM is implemented appropriately and in easier way to make a growing number of countries that took part in it to address the issue of global warming and climate change. Keywords: Carbon Trade, Global Warming, UNFCCC, Kyoto Protocol, ERPA.